Bacterial Sensitivity Pattern ?n N??n?t?l ?????? at Civil Hospital Hyderabad - Abro, Asif Zafar; Chohan, Muhammad Nadeem; Mahesar, Mumtaz (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: T? evaluate the bacterial sensitivity pattern ?n n??n?t?l ?????? at Neonatal Unit, Civil Hospital Hyderabad. METHODOLOGY: The observational Cross-sectional study was conducted at Neonatal Unit, D???rtm?nt ?f ???d??tr???, Civil H????t?l, H?d?r?b?d from 1st January to 30th June 2014. Total 332 N??n?t?? (1 – 28 d??? ?f l?f?) ??th neonatal sepsis were included in this study. N??n?t?? ?h? had ?lr??d? r????v?d ?nt?b??t??? ?nd ??th gr??? ??ng?n?t?l m?lf?rm?t??n ??r? ?x?lud?d fr?m th? ?tud?. ?ll n??n?t?? ?h? m??t th? ?n?lu???n ?r?t?r?? were investigated (??m?l?t? bl??d ??unt, ?r?thr?mb?n t?m?, & Bl??d ?ultur??). Positive Blood cultures were evaluated for their sensitivity to various antibiotics. R??ULT?: Th? m??n ?g? ??? 17.3±7 d???, 181 (54.5%) ??r? m?l? ?nd 151 (46.4%) ??r? f?m?l?, 200 (76.6%) ??r? ????? ?f ??rl? ?n??t n??n?t?l ?????? ?nd 132 (66.2%) ??r? l?t? ?n??t ??????. History of ?r?m?tur? ru?tur? ?f m?mbr?n? was present in 24.6%. Kl?b???ll? ?n?um?n??? ??? th? m??t ??mm?n ?rg?n??m ???l?t?d fr?m bl??d (39.78%) f?ll???d b? ?. ??l? (22.58%) ?nd ?t??h?l?????u? ?ur?u? (18.27%).Klebsiella was sensitive to Amikacin, Gentamycin and Ciprofloxacin in 100% cases, while it was resistant to Ampicillin in 100% cases. C?NCLU???N?: ?t ?? ??n?lud?d fr?m th?? ?tud? th?t Kl?b???ll? ??? th? m??t ??mm?n ?rg?n??m f?r n??n?t?l ?????? and it was ??n??t?v? t? ??mm?n ?nt?b??t???.